2012
DOI: 10.1021/ie2018492
|View full text |Cite
|
Sign up to set email alerts
|

Sour Corrosion of C110 Steel and Its Influence by Galvanic Couple and Stress

Abstract: Combinational metals of casing or tubing string have been extensively used in deep sour gas wells because of their corrosion resistance and low costs. C110 carbon steel and G3 alloy connected by a thread joint under different stresses represent a typical application of dissimilar metals in such a case. Around the contact part, complex corrosion can occur, including general, galvanic, and stress corrosion. To evaluate such corrosion, simulation experiments were conducted. Three specimens involving (1) a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Under external load, it has been generally agreed that the plastic strain will significantly reduce the corrosion resistance by directly enhancing the anodic reaction [7,11,14,16,[21][22][23][24][25][26] while the hydrogen evolution was reported to increase as well [21,22]. Despic et al [11] observed that a negative corrosion potential shifted by up to 30 times, with a marked increase in the anodic current density at the onset of the tensile plastic strain and reached an asymptotic value gradually.…”
Section: Introductionmentioning
confidence: 99%
“…Under external load, it has been generally agreed that the plastic strain will significantly reduce the corrosion resistance by directly enhancing the anodic reaction [7,11,14,16,[21][22][23][24][25][26] while the hydrogen evolution was reported to increase as well [21,22]. Despic et al [11] observed that a negative corrosion potential shifted by up to 30 times, with a marked increase in the anodic current density at the onset of the tensile plastic strain and reached an asymptotic value gradually.…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al [38] evaluated the use of single piece of C110 carbon steel of casing or tubing and different stresses in deep sour gas wellsunder high-pressure (65 MPa) and high-temperature (120°C) autoclave containing brine water for seven days and dissolved H 2 S, CO 2 and elemental sulfur.The results showed that complex corrosion can occur around the contact partincluding general, galvanic, and stress corrosion and the sour corrosion of C110 steel in the vapor is similar to that in solution.…”
Section: Fig (8)types Of Cracking In a Sour Environmentmentioning
confidence: 99%
“…This development leads to the exploitation of materials in extreme conditions [8][9][10][11][12], resulting in premature equipment failure [13][14][15][16][17][18] when operating in aggressive environments containing chlorine ions (Cl − ), carbon dioxide (CO 2 ), and hydrogen sulfide (H 2 S). Sulfide stress corrosion cracking (SSC), which is typical for materials in a hydrogen sulfide-containing environment, causes metal cracking under the action of corrosion and tensile stresses in the presence of moisture and hydrogen sulfide [9,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%